The Relevance of Franz L. Neumann’s Critical Theory in 2017: "Anxiety and Politics" in the New Age of Authoritarian Capitalism - Christian Fuchs (tripleC: Communication, Capitalism & Critique)
This articles discusses and contextualises tripleC’s republication of Franz L. Neumann’s essay Anxiety and Politics. It provides some background information on Neumann’s life and works. The essay ascertains that in the age of new nationalisms, rising right-wing authoritarianism and authoritarian capitalism, Franz L Neumann’s works can help us to critically understand contemporary society.